2022
DOI: 10.1017/s0033291722002835
|View full text |Cite
|
Sign up to set email alerts
|

Utility of PHQ-2, PHQ-8 and PHQ-9 for detecting major depression in primary health care: a validation study in Spain

Abstract: Background Primary health care (PHC) professionals may play a crucial role in improving early diagnosis of depressive disorders. However, only 50% of cases are detected in PHC. The most widely used screening instrument for major depression is the Patient Health Questionnaire (PHQ), including the two-, eight- and nine-item versions. Surprisingly, there is neither enough evidence about the validity of PHQ in PHC patients in Spain nor indications about how to interpret the total scores. This study aimed to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Our search identified 367 distinct articles; 26 underwent full-text review, yielding 10 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 for this systematic review ( Figure 1 ). One study 32 focused solely on the PHQ-2, 7 studies 23 , 24 , 25 , 26 , 28 , 29 , 31 evaluated the PHQ-9, and 2 studies 27 , 30 examined both the PHQ-2 and PHQ-9.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our search identified 367 distinct articles; 26 underwent full-text review, yielding 10 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 for this systematic review ( Figure 1 ). One study 32 focused solely on the PHQ-2, 7 studies 23 , 24 , 25 , 26 , 28 , 29 , 31 evaluated the PHQ-9, and 2 studies 27 , 30 examined both the PHQ-2 and PHQ-9.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, given the paucity of studies identified in this review, we were unable to evaluate the performance of the PHQ-2 and PHQ-9 compared with each standardized clinical interview, which may be understudied in Spanish-speaking or specific subpopulations . Finally, of all 10 studies in this review, not 1 measured the test-retest reliability; thus, conclusions on consistency of screening tests through time are difficult to make.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations